1995
DOI: 10.1002/ajmg.1320560215
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trends of sleep‐disordered breathing in Prader‐Willi syndrome: The role of obesity

Abstract: Polysomnographic recordings of 43 children and adults with Prader-Willi syndrome (PWS) were inspected and classified into 5 age groups. The effect of age and body mass index (BMI) on measures of breathing, oxygen saturation, and sleep efficiency were analyzed. Body mass index (BMI) increased significantly between early childhood and preadolescent groups. Subjecting the data to analysis of variance showed an overall significant effect of BMI but no age effect on breathing parameters and oxygen saturation. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(25 citation statements)
references
References 7 publications
1
23
0
1
Order By: Relevance
“…[5][6][7] The sleep-disordered breathing was mainly obstructive in type, as evidenced by a high frequency of snoring, inspiratory flow limitation, and obstructive apneas and hypopneas occurring mainly in REM sleep. In keeping with previous reports, 1,6,9 there was a correlation between obesity and features of sleep apnea, such as sleep hypoxemia and sleep disruption. Sustained partial upper airway obstruction was present, as evidenced by persistent snoring and inspiratory flow limitation in many subjects, even those without significant sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7] The sleep-disordered breathing was mainly obstructive in type, as evidenced by a high frequency of snoring, inspiratory flow limitation, and obstructive apneas and hypopneas occurring mainly in REM sleep. In keeping with previous reports, 1,6,9 there was a correlation between obesity and features of sleep apnea, such as sleep hypoxemia and sleep disruption. Sustained partial upper airway obstruction was present, as evidenced by persistent snoring and inspiratory flow limitation in many subjects, even those without significant sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…(J Pediatr 2005;147:823-9) A lthough early reports suggested that sleep-disordered breathing was uncommon in Prader-Willi syndrome (PWS), 1-4 most recent studies [5][6][7] (although not all 8 ) have found that it is in fact common, especially during rapid eye movement (REM) sleep. 5,6,9 However, uncertainty remains regarding the nature and causes of sleepdisordered breathing in PWS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Inset shows whole-cell and integrated nerve recordings during a single inspiratory burst. sleepiness in childhood and adulthood that is characteristic of PWS (Hertz et al, 1995). Aside from one report showing reduced number of oxytocin neurons in the hypothalamic paraventricular nucleus, no abnormal pathological findings have been noted in PWS individuals at autopsy (Swaab et al, 1995).…”
Section: Figurementioning
confidence: 95%